Analysis of T-cell alloantigen response via a direct pathway in kidney transplant recipients with donor-specific antibodies - Iwahara, Naoya; Hotta, Kiyohiko; Iwami, Daiki; Tanabe, Tatsu; Tanaka, Yuka; Ito, Yoichi M.; Otsuka, Takuya; Murai, Sachiyo; Takada, Yusuke; Higuchi, Haruka; Sasaki, Hajime; Hirose, Takayuki; et al. (Frontiers in Immunology, 2023)
Donor-specific antibodies (DSAs) are the main cause of graft loss over time. The direct pathway of alloantigen recognition is important in the pathogenesis of acute rejection. Recent studies have suggested that the direct pathway also contributes to the pathogenesis of chronic injury. Nevertheless, there are no reports on T-cell alloantigen response via the direct pathway in kidney recipients with DSAs. We analyzed the T-cell alloantigen response via the direct pathway in kidney recipients with DSAs (DSA+) or without DSAs (DSA−). A mixed lymphocyte reaction assay was implemented to assess the direct pathway response. DSA+ patients showed significantly higher CD8+ and CD4+ T cell responses to donor cells than DSA− patients. Furthermore, proliferating CD4+ T cells showed a marked increase in Th1 and Th17 responses in DSA+ patients than in DSA− patients. In a comparison between anti-donor and third-party responses, the anti-donor CD8+ and CD4+ T cell response was significantly lower than the anti-third-party response. In contrast, the donor-specific hyporesponsiveness was absent in DSA+ patients. Our study demonstrated that DSA+ recipients have a greater potential for developing immune responses against the donor tissues via the direct alloantigen recognition pathway. These data contribute to an understanding of DSAs pathogenicity during kidney transplantation.